Evaluation of Outdoor Air Pollution Impact on Children’s Health - Zagorje ob Savi Case - Kukec, Andreja; Farkaš-Lainščak, Jerneja; Zaletel-Kragelj, Lijana (Anali PAZU, 2022)
Outdoor air pollution is one of major public health concerns of today. Regarding outdoor air pollution, children are one of the most vulnerable groups. The aim of our study was to assess temporal association between number of consultations due to respiratory diseases in children and outdoor air pollution in municipality of Zagorje ob Savi. A time-trend ecological study was carried out for the period between January 1, 2006 and December 31, 2011. The study population consisted of children, aged 1-11 years, residing in the municipality of Zagorje ob Savi, who visited the Community Health Centre due to respiratory diseases. Immission data were obtained from the fixed measuring station in the municipality of Zagorje ob Savi. The association between the observed outcome, explanatory factors and covariates was analysed using Poisson regression model. The results of multi-pollutant model showed that in municipality of Zagorje ob Savi is a positive temporal association between the number of consultations and concentration of particulate matter 10 micrometers in diameter (p<0.001) and concentration of ozone (p=0.003).